Characterization of occupational exposure to fungal burden in Portuguese bakeries - Viegas, Carla (2019)
Several studies reported adverse respiratory health effects in workers exposed to ambient contaminants in bakeries. The aim of this study was to examine worker exposure to fungi and mycotoxins in Portuguese bakeries in order to develop new policies in occupational health. Environmental samples such as air, surfaces, settled dust and electrostatic dust collector (EDC) were collected in 13 bakeries for fungal and mycotoxins assessment. Air samples obtained by impaction were performed applying malt extract agar (MEA) supplemented with chloramphenicol (0.05%) and dichloran glycerol (DG18) agar-based media. Air samples collected through impinger method were determined as well for fungal detection by molecular tools of Aspergillus sections and mycotoxins. The highest median value for fungal load was 1053 CFU·m-3 and 65.3% (32 out of 49) of the sampling sites displayed higher fungal load than limits imposed by the World Health Organization. Aspergillus genera was found in air, surface swabs and EDC. Molecular tools were effective in measuring Aspergillus section Fumigati in 22.4% on air, 27.8% on surface swabs and in 7.4% in EDC and Aspergillus section Versicolores in one air sample. All settled dust samples showed contamination with six to eight mycotoxins in each sample. The mycotoxins detected were deoxynivalenol-3-glucoside, deoxynivalenol, zearalenone, 15-acetyldeoxynivalenol, monoacetoxyscirpenol, diacetoxyscirpenol, fumonisin B1, fumonisin B2, griseofulvin, HT2, ochratoxin A, ochratoxin B and mycophenolic acid. Industrial hygienists and exposure assessors should rely on different sampling methods (active and passive) and different assays (culture based and molecular methods) to obtain an accurate risk characterization regarding fungal burden (fungi and mycotoxins). Additionally, the awareness for the raw material as a potential mycotoxins indoor contamination source is important.